ALSTONIA MACROPHYLLA (APOCYNACEAE): A NEW RECORD OF NATURALIZED SPECIES IN JAVA, INDONESIA - Surianto Effendi; Wendy Achmmad Mustaqim (Floribunda, 2021)
Surianto Effendi & Wendy A. Mustaqim. 2021.  Alstonia macrophylla (Apocynaceae): A New Record of Naturalized Species in Java, Indonesia. Floribunda 6(6):  207–212. — Alstonia macrophylla (Apocynaceae), a Malesian widespread species tree, here for the first time is formally reported to be naturally found in Java. The report is based on plants growing in the Ciampea limestone hills, Ciampea sub-district, west of Bogor, West Java. Description, ecology, illustration and a brief discussion regarding the occurrence state of this species as naturalized species in Java are presented. A key to Alstonia species in Java is also given.